2015
DOI: 10.1186/s12918-015-0223-6
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Th17 cell differentiation dynamics using a novel integrative modeling framework for time-course RNA sequencing data

Abstract: BackgroundThe differentiation of naive CD 4+ helper T (Th) cells into effector Th17 cells is steered by extracellular cytokines that activate and control the lineage specific transcriptional program. While the inducing cytokine signals and core transcription factors driving the differentiation towards Th17 lineage are well known, detailed mechanistic interactions between the key components are poorly understood.ResultsWe develop an integrative modeling framework which combines RNA sequencing data with mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Mechanistic models are capable of describing the actual molecular dynamics originating from reaction kinetics and the underlying network structure can also be accurately estimated by combining these models with appropriate statistical techniques (see e.g. Intosalmi et al , 2015 ; Schulz et al , 2009 ; Xu et al , 2010 ). Typically, a mechanistic model consists of a set of interacting molecular components and a formal description for the possible mechanisms affecting the time-evolution of the components.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic models are capable of describing the actual molecular dynamics originating from reaction kinetics and the underlying network structure can also be accurately estimated by combining these models with appropriate statistical techniques (see e.g. Intosalmi et al , 2015 ; Schulz et al , 2009 ; Xu et al , 2010 ). Typically, a mechanistic model consists of a set of interacting molecular components and a formal description for the possible mechanisms affecting the time-evolution of the components.…”
Section: Introductionmentioning
confidence: 99%
“…Early mathematical models of this differentiation process utilized ordinary differential equations (ODE) and were developed from existing knowledge [22,23]. More recently different modeling techniques have been used, including logical network models [24,25], and increasingly, experimental data have been used to drive the models [26,27]. …”
Section: Differentiation Of Cytokine-producing Cells and The Contrmentioning
confidence: 99%
“…In another approach aimed at investigating Th17 differentiation the authors used a RNASeq dataset generated over a detailed time course to explore the validity of several potential models [27]. In this study a dynamic ODE model of Th17 differentiation was used as a framework and four hypothetical mechanisms were identified that resulted in 12 alternative models for the molecular interactions important for Th17 differentiation.…”
Section: Differentiation Of Cytokine-producing Cells and The Contrmentioning
confidence: 99%
See 1 more Smart Citation
“…While being useful in building a general understanding of different mechanisms across the scales, most of these approaches do not allow experimentally-based model construction and validation. Experimentally-based model construction approaches have been successfully applied in the context of mechanistic modeling of molecular mechanisms (Schulz et al, 2009;Intosalmi et al, 2015;Chan et al, 2016) and extending these approaches to more complex multiscale models will be essential for methodological advancement in systems biology (Skupin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%